Magnetic bearings and bearingless drives - Chiba, Akira, 1938- (Amsterdam ; London : Elsevier/Newnes, 2005)
The application of bearingless drives is emerging as an important technique in the areas of high-speed machinery and motion-control, and this book aims to provide a thorough grounding in the principles behind this cutting-edge technology. Basic principles are described in detail with practical examples to aid understanding, and the different types of bearingless drives are introduced, along with coverage of test machines and applications. Aimed at practising electrical and mechanical engineers and advanced students, Magnetic Bearings and Bearingless Drives provides an essential guide to an area of engineering previously only fully covered by large numbers of academic papers. Unique and comprehensive coverage of a cutting-edge subject for electrical and mechanical engineers A reference text and survey for designers, manufacturers and users of high-speed motors, generators and electrical drive systems Examines the basic principles behind magnetic bearings, with key technologies and applications illustrated through examples and case studies.
Introduction; Electro-magnetics and Mathematical Model of Magnetic; Magnetic bearing controllers; Mechanical Dynamics; Power Electronics Circuits for Magnetic Bearings; Primitive Model and control strategy of bearingless motors; Analysis in rotational coordinates and magnetic suspension strategy for bearingless drives with 4-pole and 2-pole windings; Field Orientation, VA requirement and magnetic saturation; Cylindrical Permanent Magnet Synchronous Bearingless Motors; Inset-type Permanent Magnet Bearingless Motors; Buried Permanent Magnet Bearingless Motors; Synchronous Reluctance Bearingless Motors; Bearingless Induction Motors; Homopolar, Hybrid and Consequent-pole Bearingless Motors; Switched Reluctance Bearingless Motors; Winding Arrangement Variations; Mechanical Structure and Position Regulation; Displacement Sensors and Sensorless operation; Controllers and Power Electronics; Design Procedure and examples; Applications and test machines; Appendices; Index.
Includes bibliographical references and index.
Keywords: Magnetic bearings; Power transmission; Electronic books